2019
DOI: 10.1039/c8nr08400a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of pixelated liquid crystal nanostructures employing the contact line instabilities of droplets

Abstract: A single-step room-temperature fabrication method is presented to develop a collection of ordered LC micro-/nanodroplets over a large surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…25,26 Some research have also been done on the contact line instability of LC drop on solid substrates. [27][28][29][30] Herminghaus et al have also reported instantaneous room temperature dewetting of 5AB 4 (which undergoes direct phase transition from crystalline phase to isotropic phase at T z 10 C) thin lms transferred from an LB trough to a silicon substrate. Clear signatures of both nucleated and spinodal dewetting were observed during the dewetting of the lm.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Some research have also been done on the contact line instability of LC drop on solid substrates. [27][28][29][30] Herminghaus et al have also reported instantaneous room temperature dewetting of 5AB 4 (which undergoes direct phase transition from crystalline phase to isotropic phase at T z 10 C) thin lms transferred from an LB trough to a silicon substrate. Clear signatures of both nucleated and spinodal dewetting were observed during the dewetting of the lm.…”
Section: Introductionmentioning
confidence: 99%
“…28 A few recent studies uncover that the same can also be achieved under a solvent exposure at room temperature. 29 Subsequently, self-organization 30 under long-range interactions and spin dewetting 31 of an LC film on a patterned surface are the other alternative routes leading to an ordered array of LC droplets. Once such droplet arrays are formed, the transmission of polarized light rays through such LC droplets can indeed be controlled through a solvent exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid marbles can also interact with light to create optically responsive reactors , or light-driven delivery vehicles. , We hypothesize that compound lenses inspired by the mosquito eye can be created by combining the mobility and stability of liquid marbles with the monodispersity and large-scale production of droplet-based microfluidic devices. In addition, a chemically patterned substrate can host and localize multiple sessile droplets where each could serve as the hemispherical dome structures of compound lenses, leading to a scalable process. …”
Section: Introductionmentioning
confidence: 99%